(untitled) (American Journal of Education and Technology, 2023)
A country’s foundation is its educational system. Without education, no country can advance since it teaches knowledge and abilities that improve quality of life and human growth. Women’s education is essential to society and to a country. Investment in preparing the workforce of the future is very essential in a developing nation like Bangladesh, which is one of the most promising emerging economies. Education is a fundamental human right, but in a developing country like Bangladesh, special focus must be placed on the education of women. Women who pursue education will not only have higher household incomes and help create a more skilled labor force, but they will also have greater social mobility. The value of education to our nation cannot be overstated. Therefore, government should focus more on the issue. Given that women make up half of our population, this essay will examine the situation of women’s education in Bangladesh. This investigation into the advancement of women’s education and the resources made available by the Bangladeshi government was carried out through the analysis of documents. It will encourage researchers to look further into the education and development of women.